2016
DOI: 10.1038/nrcardio.2016.19
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndromes without coronary plaque rupture

Abstract: The latest advances in plaque imaging have provided clinicians with opportunities to treat acute coronary syndrome (ACS) and provide individualized treatment recommendations based not only on clinical manifestations, angiographic characteristics, and biomarker data, but also on the findings of plaque morphology. Although a substantial proportion of ACS events originate from plaques with an intact fibrous cap (IFC), clinicians predominantly equate ACS with plaque rupture arising from thin-cap fibroatheromas. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 78 publications
1
18
0
5
Order By: Relevance
“…Thrombus formation due to coronary spasms has been reported as one of the mechanisms responsible for ACS without plaque rupture [2][3][4], with the findings of the present case supporting the presence of coronary spasm-induced thrombus formation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Thrombus formation due to coronary spasms has been reported as one of the mechanisms responsible for ACS without plaque rupture [2][3][4], with the findings of the present case supporting the presence of coronary spasm-induced thrombus formation.…”
Section: Discussionsupporting
confidence: 74%
“…In cases with coronary plaque rupture, coronary spasm may cause plaque rupture mediated by the external force of the coronary spasm itself; and this relationship was confirmed in an autopsy case report [7]. On the other hand, coronary erosions without plaque rupture are thought to contribute to coronary spasminduced thrombus formation [2][3][4]. Using CAS, Etuda et al [5] reported that intracoronary abnormalities, such as intracoronary hemorrhage, intimal flap, thrombus, or ulcers, were present in 40% of cases with variant angina, which is thought to be a type of angina with a high coronary spasm activity.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Unfortunately, our current experimental models in hypercholesterolemic mice fail to emulate many of the key features of plaque erosion (i.e., endothelial desquamation, neutrophil recruitment, few macrophages, and small necrotic core). 4 However, a recent study found that a combination of vascular injury followed by flow disruption recapitulated many of the characteristics of eroded plaques, a strategy that may be a valuable tool to probe anti-inflammatory therapies moving forward. 5 It is important to note that even if there were a trend toward reduced relative risk of plaque erosion in these patients, plaque rupture of thin-capped fibroatheromas (TCFAs) – also known as “vulnerable plaques” – remains the primary modality for atherosclerosis complications and still requires extensive research focus.…”
Section: Interpreting the Mode Of Lesion Failurementioning
confidence: 99%
“…Estimates on the prevalence of plaque erosion and rupture vary, but even aggressive estimates suggest that rupture remains the primary driver of plaque failure. Indeed, a ruptured fibrous cap is found in ~2/3 of post-mortem samples from patients dying of an acute coronary syndrome 4 and intravascular imaging has shown that plaque rupture accounts for ~71% and 43% of ST and non-STEMI, respectively. 3 Although the PROSPECT study showed that only 5% of TCFAs resulted in a clinical event in 3.4 years, TCFA plaque morphology was the only independent risk factor that was predictive for a future event.…”
Section: Interpreting the Mode Of Lesion Failurementioning
confidence: 99%